1993
DOI: 10.1029/92ja01665
|View full text |Cite
|
Sign up to set email alerts
|

First simultaneous measurements of neutral and ionized iron densities in the upper mesosphere

Abstract: We report on the results of a multi‐instrument study of a sporadic Fe layer and a sporadic E layer which took place in the night of September 20, 1991, at the Andøya Rocket Range (69°N, 16°E). A ground‐based lidar was used to measure mesospheric Fe densities, while simultaneously rocket‐borne probes and an ion mass spectrometer measured the profile of total ion density and ion composition, respectively. All instruments observed the sporadic layers near 97 km altitude. Radar tracking of chaff clouds established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…For the case of sodium, Friedman et al (2000) report on Na enrichments below 97 km without the occurrence of Na + layers in the same volume. Height differences between ionized and neutral sporadic metal layers have been reported by Alpers et al (1993) and Gardner et al (1993). Alpers et al (1993) measured the altitude of a Fe s layer by lidar and that of a simultaneous Fe + s layer by a rocket-borne mass spectrometer.…”
Section: Discussion Of the Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the case of sodium, Friedman et al (2000) report on Na enrichments below 97 km without the occurrence of Na + layers in the same volume. Height differences between ionized and neutral sporadic metal layers have been reported by Alpers et al (1993) and Gardner et al (1993). Alpers et al (1993) measured the altitude of a Fe s layer by lidar and that of a simultaneous Fe + s layer by a rocket-borne mass spectrometer.…”
Section: Discussion Of the Observationsmentioning
confidence: 99%
“…Height differences between ionized and neutral sporadic metal layers have been reported by Alpers et al (1993) and Gardner et al (1993). Alpers et al (1993) measured the altitude of a Fe s layer by lidar and that of a simultaneous Fe + s layer by a rocket-borne mass spectrometer. They found the neutral layer 1 km higher than the ionized layer.…”
Section: Discussion Of the Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar rocket measurements were reported by Narcisi and Bailey (1965) and Narcisi (1967), including a¯ight during the Leonid meteor shower which conclusively demonstrated that meteor ablation is the mechanism responsible for production of metallic ions in the upper atmosphere. Numerous other rocket¯ights have subsequently provided data on metallic ion distributions (i.e., Young et al, 1967;Aiken and Goldberg, 1973;Aiken et al, 1974Aiken et al, , 1977Goldberg and Witt, 1977;Zbinden et al, 1975;Alpers et al, 1993). Some of these provided evidence for connections between metallic ion layers and sporadic-E (E s ), and others attempted to establish connections between metallic ion cluster molecules and the formation of noctilucent clouds.…”
Section: Brief History Of Observational Workmentioning
confidence: 99%